James Ferguson and His Critique on Modernity - Al Isra, Andi Batara (Glocal Society Journal, 2024)
The book review reveals the issue of modernity from James Ferguson’s Expectation of Modernity: Myths and Meanings of Urban Life on the Zambian Copperbelt, which is heartbreaking and heartbreaking.  This well-written and thick seven-chapter book is based on Ferguson’s ethnographic fieldwork in Copperbelt, Zambia, between the 1970s and 1990s. The book introduced what is called the ethnography of decline, a way of understanding people’s point of view about their own experience of social, cultural, and economic ‘advance’ and ‘decline’. It is a very hard task for ethnographers since they must deal with the situation instead of working with people. Related to that, Ferguson also explores a concept called ‘abjection’, a process of being thrown (down) aside, expelled, or discarded. Using this concept, he claims that modernity is quite similar to colonialism, which brings the dichotomy of ‘the West’ and ‘the rest’ where the West is ‘modern,’ and the rest is ‘savage’. Thus, the globalization of the economy brought about by modernization has been experienced as abjection and disconnection, concluding that modernity is no more than a myth that would never exist.